Reflections of ibadah camp 2025 - Mhd. Sarif, Suhaimi; Man, Siti Mariam (Sejahtera Consumerism Kulliyyah of Economics and Management Sciences IIUM, 2025)
The KENMS Ibadah Camp 2025 represents a vital spiritual platform that strengthens ukhuwwah, nurtures resilience, and reinforces collective identity within the Kulliyyah. Yet, participant feedback reveals the need for systematic improvements to sustain its transformative impact. This report argues that the upcoming KENMS Ibadah Camp 2026 must adopt a more focused programme design, enriched spiritual content, greater inclusivity, stronger logistical coordination, and clearer committee accountability. Feedback indicates that excessively packed schedules, night sessions, and physically strenuous activities compromised participant comfort and diluted the spiritual essence of the camp. Therefore, streamlining activities within office hours and extending the camp over 2.5 to 3 days would balance physical well-being with spiritual intensity. Enhancing core spiritual elements—such as qiyamullail, solat berjamaah, Qur’an recitation, and tazkirah—remains essential for achieving the camp’s objectives. Inclusivity must also be prioritized by selecting accessible venues, minimizing physical strain, and offering optional accommodation for qiyamullail. Furthermore, Islamic ethical considerations, particularly the prohibition of tabarruj, underscore the need to refine award categories and ensure that all practices align with Shariah values. Collectively, these improvements will strengthen the spiritual, social, and organizational outcomes of future Ibadah Camps, ensuring that the programme continues to inspire, unite, and elevate the KENMS community.